Aural comprehension and oral production of young EFL learners - Lopriore, Lucilla; Mihaljević-Djigunović, Jelena (2011)
Oral language is seen as the basis for establishing the new language in young learners. Hence the focus on oracy in early FL programmes. This This paper looks into aural comprehension and oral production of young FL learners. The study whose findings are reported was carried out in Croatia and Italy. Over 90 young EFL learners participated in the study. They were drawn from metropolitan, small town and rural schools in each of the two country contexts. The participants' aural comprehension was measured by means of two types of tasks. The first consisted of multiple choice items, each accompanied with three pictures. The second included true/false statements about one complex picture. The tasks were intended to measure the ability to identify specific vocabulary items and comprehension of short chunks supported by visuals. Data on oral production was gathered by means of an interactive task (a guess who game) measuring participants' language in terms of lexical diversity and syntactic complexity. Results on the aural and oral tasks were compared for each learner. Comparisons were also made taking into account the young participants' individual differences (attitudes, motivation, linguistic self-concept) as well as the differences in the contexts in which they were learning EFL (teaching quality, exposure to English, home support, SES).
Projekt MZOS
ENG